Method for Extraction and Quantification of Metal-Based Nanoparticles in Biological Media: Number-Based Biodistribution and Bioconcentration - Abdolahpur Monikh, Fazel; Chupani, Latifeh; Zusková, Eliska; Peters, Ruud; Vancová, Marie; Vijver, Martina G; Porcal, Petr; Peijnenburg, Willie J G M (Environmental science & technology, 2019)
A multistep sample preparation method was developed to separate metal-based engineered nanoparticles (ENPs) from biological samples. The method was developed using spiked zebrafish tissues and standard titanium dioxide (TiO2) and cerium dioxide (CeO2) ENPs. Single-particle inductively coupled plasma mass spectrometry was used to quantify the separated particles in terms of number concentration. This method demonstrated mass recoveries of more than 90% and did not strikingly alter the median particles size. High number recoveries were calculated for CeO2 ENPs (>84%). Particle number recoveries were poor for TiO2 ENPs (<25%), which could be due to the interference of 48Ca with the measured isotope 48Ti. The method was verified using zebrafish exposed to CeO2 ENPs to test its applicability for nanotoxicokinetic investigations. Total mass of Ce and particle number concentration of CeO2 ENPs were measured in different tissues. Notably, the mass-based biodistribution of Ce in the tissues did not follow the number-based biodistribution of CeO2. Moreover, the calculated mass-based bioconcentration factors showed a different pattern in comparison to the number-based bioconcentration factors. Our findings suggest that considering mass as the sole dose-metric may not provide sufficient information to investigate toxicity and toxicokinetics of ENPs.
Keywords: cer; Cerium; Spectrum Analysis; Nanoparticles; tkáňová distribuce; spektrální analýza; Tissue Distribution; Particle Size; kovové nanočástice; Metal Nanoparticles; nanočástice; velikost částic